The Influence of Financial Literacy on The Consumer Behavior of Housewives in Sirombu Village Sirombu District West Nias Regency - Marulafau, Imadulhaq; Telaumbanua, Aferiaman; Bate'e, Maria Magdalena; Harefa, Idarni (ProBisnis : Jurnal Manajemen, 2025)
Poor financial management often triggers economic instability and disrupts household harmony, particularly when housewives engage in consumptive behavior. This study examines the effect of financial literacy on the consumptive behavior of housewives in Sirombu Village, West Nias Regency. Using a quantitative associative method, the research involved 74 respondents selected through purposive sampling. Data were collected through Likert-scale questionnaires and analyzed using simple linear regression. The findings reveal that financial literacy significantly and negatively affects consumptive behavior, as represented by the regression equation Y = 60.023 – 0.472X. The coefficient of determination (R²) indicates that financial literacy contributes 43.9% to reducing consumptive tendencies, while the remaining 56.1% is influenced by other external factors. These results confirm that higher levels of financial literacy enable housewives to manage expenses wisely, distinguish between needs and desires, and prevent impulsive consumption. The study highlights the urgent need for financial education programs in rural areas to strengthen household financial resilience and support sustainable family welfare.